1999
DOI: 10.1128/mcb.19.10.6523
|View full text |Cite
|
Sign up to set email alerts
|

AnCF, the CCAAT Binding Complex of Aspergillus nidulans, Is Essential for the Formation of a DNase I-Hypersensitive Site in the 5′ Region of the amdS Gene

Abstract: The CCAAT sequence in the amdS promoter ofAspergillus nidulans is recognized by AnCF, a complex consisting of the three evolutionary conserved subunits HapB, HapC, and HapE. In this study we have investigated the effect of AnCF on the chromatin structure of the amdS gene. The AnCF complex and the CCAAT sequence were found to be necessary for the formation of a nucleosome-free, DNase I-hypersensitive region in the 5′ region of theamdS gene. Deletion of the hapE gene results in loss of the DNase I-hypersensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 77 publications
2
28
0
1
Order By: Relevance
“…AnCF acts at CCAAT sequences to affect the expression of a diverse array of genes with no obvious common role in metabolism (7). Binding of AnCF to a CCAAT sequence in the 5Ј region of the amdS gene has been shown to result in the formation of a nucleosome-free region (32). Here, we have shown that AcuFLacZ expression is greatly reduced in a strain with a deletion in the gene encoding the HapC subunit of AnCF.…”
Section: Vol 184 2002 Phosphoenolpyruvate Carboxykinase Of a Nidulansmentioning
confidence: 65%
“…AnCF acts at CCAAT sequences to affect the expression of a diverse array of genes with no obvious common role in metabolism (7). Binding of AnCF to a CCAAT sequence in the 5Ј region of the amdS gene has been shown to result in the formation of a nucleosome-free region (32). Here, we have shown that AcuFLacZ expression is greatly reduced in a strain with a deletion in the gene encoding the HapC subunit of AnCF.…”
Section: Vol 184 2002 Phosphoenolpyruvate Carboxykinase Of a Nidulansmentioning
confidence: 65%
“…A similar mechanism has been shown for the regulation of the alcA gene of A. niger, where the transcriptional activator AlcR competes with CreA for the corresponding, partially overlapping binding sites (e.g. Marmorstein et al 1992;Marmorstein and Harrison 1994;Mathieu and Felenbok 1994;Narendja et al 1999). …”
Section: Interplay Of Xyr1 With Specific Transcriptional Regulators Amentioning
confidence: 95%
“…The Hap2/3/5 complex contacts the CCAAT box within this motif. The CCAAT box, which is present in many fungal promoters (Brakhage et al 1999), was shown to be involved in the maintenance of an active chromatin structure (Narendja et al 1999). On the other hand, CCAAT boxes in filamentous fungi showing repressing functions (e.g.…”
Section: Interplay Of Xyr1 With Specific Transcriptional Regulators Amentioning
confidence: 99%
“…The Hap2/3/5-binding CCAAT motif in XAE is a common cis-acting element found in the promoter and enhancer regions of a large number of eukaryotic genes (20), including filamentous fungi (3), and has been shown to be involved in maintaining a transcriptionally active chromatin structure (24). We have recently shown that the CCAAT-box within the CAE of H. jecorina cbh2 is involved in nucleosome assembly (S. Zeilinger, M. Leonhartsberger, M. Pail, R. L. Mach, and C. P. Kubicek, unpublished data) and that a mutation of CCAAT to CCCTT within CAE results in a 30% decrease in gene transcription (43).…”
mentioning
confidence: 99%